Being Interdisciplinary Adventures in urban science and beyond - Wilson, Alan (UCL Press, 2022)
In Being Interdisciplinary, Alan Wilson draws on five decades as a leading figure in urban science to set out a systems approach to interdisciplinarity for those conducting research in this and other fields. He argues that most research is interdisciplinary at base, and that a systems perspective is particularly appropriate for collaboration because it fosters an outlook that sees beyond disciplines. There is a more subtle thread, too. A systems approach enables researchers to identify the game-changers of the past as a basis for thinking outside convention, for learning how to do something new and how to be ambitious, in a nutshell how to be creative. Ultimately, the ideas presented address how to do research. Building on this systems focus, the book first establishes the basics of interdisciplinarity. Then, by drawing on the author's experience of doing interdisciplinary research, and working from his personal toolkit, it offers general principles and a framework from which researchers can build their own interdisciplinary toolkit, with elements ranging from explorations of game-changers in research to superconcepts. In the last section, the book tackles questions of managing and organising research from individual to institutional scales. Alan Wilson deploys his wide experience - researcher in urban science, university professor and vice-chancellor, civil servant and institute director - to build the narrative. While his experience in urban science provides the illustrations, the principles apply across many research fields.